2022
DOI: 10.1111/1365-2435.14101
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal dissolved organic matter release by turf algae and its role in the microbialization of reefs

Abstract: 1. The increased release of dissolved organic matter (DOM) by algae has been associated with the fast but inefficient growth of opportunistic microbial pathogens and the ongoing degradation of coral reefs. Turf algae (consortia of microalgae and macroalgae commonly including cyanobacteria) dominate benthic communities on many reefs worldwide. Opposite to other reef algae that predominantly release DOM during the day, turf algae containing cyanobacteria may additionally release large amounts of DOM at night. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…It is paramount to understand BCM structure and function to be able to assess how community dynamics are created and sustained through biogeochemical gradients. Benthic cyanobacterial mat communities create feedback loops that facilitate mat proliferation, even releasing copious amounts of carbon and nitrogen back into the environment (Brocke et al, 2015(Brocke et al, , 2018Mueller et al, 2022). Mechanisms of how these feedback loops are connected to broader biogeochemical cycles and for the uptake and release of other elements such as sulfur still remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is paramount to understand BCM structure and function to be able to assess how community dynamics are created and sustained through biogeochemical gradients. Benthic cyanobacterial mat communities create feedback loops that facilitate mat proliferation, even releasing copious amounts of carbon and nitrogen back into the environment (Brocke et al, 2015(Brocke et al, , 2018Mueller et al, 2022). Mechanisms of how these feedback loops are connected to broader biogeochemical cycles and for the uptake and release of other elements such as sulfur still remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparison of mats in multiple different flow environments is necessary for our understanding of how diversity, complexity, and niche structure changes in response to flow speed. Although we know from Mueller et al (2022) that BCMs can release excess dissolved organic matter and create hypoxic conditions at their surface, we still lack an understanding of DBL thickness, longevity, and the effects an anoxic DBL will have on other mat community members, competitors, and consumers. Most publications have examined the effects of oxygen concentrations within DBLs (e.g., Dillon et al, 2009;van Erk et al, 2023).…”
Section: Flow Speed and Dbls Affect Mat Structure And Niche Partitioningmentioning
confidence: 99%
“…The apparent higher DOC consumption may just be the result of lower release rates of DOC by corals during the night, shifting the balance between uptake and release toward net uptake. Indeed, in algae, but also corals, the release of photosynthetically fixed carbon in the form of DOC has been shown to be directly related to primary production, with a positive relationship between DOC release and light availability (e.g., Kurihara et al 2018; Mueller et al 2022). During the day, photosynthesis can meet more than 100% of the respiratory needs of hexacorals, which therefore release the excess carbon as DOC and mucus (Davies 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Mat‐building cyanobacteria can rapidly take up and utilize environmental nutrients relative to macroalgal competitors, likely exacerbating their contribution to reef productivity (den Haan et al., 2016). However, it was also recently demonstrated that benthic cyanobacterial mats, at least on Caribbean reefs, release a great deal of this fixed carbon back into their surrounding reef environment as Dissolved Organic Carbon (DOC) and thus act as net sources of DOC, especially during the night (Brocke et al., 2015; Mueller et al., 2022). This algal‐derived DOC is more readily bioavailable to microbes and sponges on reefs and fuels inefficient carbon metabolism compared to coral‐derived DOC, which can play a role in the expansion of opportunistic pathogens on reefs and contribute to overall reef microbialization (Haas et al., 2016; Silva et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria, however, can also be predominant members of the prokaryotic assemblage within turf algal communities, alongside a dominance of Proteobacteria (predominantly Alphaproteobacteria), Bacterioidota, and Firmicutes (Barott et al., 2011; Hester et al., 2016). Indeed, shifts in turf composition toward higher cyanobacterial dominance can skew turf algal carbon cycling toward net DOC release (Mueller et al., 2022), which can contain cyanobacteria taxonomically similar to those known to be dominant mat‐building cyanobacteria (Fricke et al., 2011). Few papers, however, have simultaneously examined the prokaryotic assemblage structure in benthic cyanobacterial aggregations and turf algae to define overlap and resolve distinctions between the prokaryotic assemblage well—and namely the cyanobacterial component—of these two critical function groups well.…”
Section: Introductionmentioning
confidence: 99%